'Hurry up please, it's time!' A psychogeography of a decommissioned university campus. Issue 6 (17th August 2020) - Kelly, Frances
ABSTRACT: This paper takes a soon-to-be disestablished satellite university campus as its site of enquiry. The campus has been an educational institution since the early twentieth century. Shortly it will be decommissioned, its future undetermined; at this moment in time it seems fitting to critically reflect on this place and the ideas and work of teaching that have shaped its material form. Using the methodology of an attentive walk from psychogeography, I attend to places and things on the campus which have furthered the work of teaching, allowing for moments of critical nostalgia. This involves looking backward and reflecting on the history of the site, with the critical aim to draw attention to limitations of contemporary hegemonic practices and discourses relating to time in the university, which prioritise its economic function (Adam 1998). Attending to everyday objects recognises the significance of ordinary materialities in teachers' working lives, present and past.